Will Mergers and Acquisition Vacillate the Performance of Banks? A Case Study of Public Sector Banks in India - Roopesh Roopesh; Sandhya Sandhya (Binus Business Review, 2022)
The recent change that the banking sector sees is the mergers and acquisitions occurring among the public sector banks. Merger and acquisition in the banking sector are part of the reform strategies to improve financial stability and gain smooth operational flow and synergy advantages. The research focused on the aspects of the banks' profitability, solvency, investment, and liquidity in the pre-and post-merger period. The research attempted to understand the varied reasons behind their mergers, acquisition, and success rate. Â The main objective was to understand the impact of synergy on the performance and profitability of banks. It was an exploratory research to understand the various objectives of mergers and to map the outcome of those objectives. Â The analysis was done through ratio analysis and paired t-test to gauge the impact of the pre-and post-merger scenario. The results find that the merger and acquisition are a positive move for some banks. However, there are certain banks which are coping at a slow pace with the synergy. The research also discovers that the synergy amongst the banks reacts in a varied way based on the objective of the mergers. The results indicate that the banks cope with the merger and acquisition at a varied pace due to various factors like Non-Performing Asset (NPA), debts, assets, and market share variabilities amongst the banks. The recent pandemic that the world faces can also be considered a factor for slower coping.